Selective copper(II) acetate and potassium iodide catalyzed oxidation of aminals to dihydroquinazoline and quinazolinone alkaloids - Richers, Matthew T.; Zhao, Chenfei; Seidel, Daniel (Beilstein Journal of Organic Chemistry, 2013)
Copper(II) acetate/acetic acid/O2 and potassium iodide/tert-butylhydroperoxide systems are shown to affect the selective oxidation of ring-fused aminals to dihydroquinazolines and quinazolinones, respectively. These methods enable the facile preparation of a number of quinazoline alkaloid natural products and their analogues.
Keywords: aminal; copper; oxygen; tert-butylhydroperoxide; quinazoline alkaloid